Estimation of overpressures from porosity based method : a theoretical approach applied to the central/coastal swamp depo-belts of the Niger delta basin - Mkpese, Ubon (International Journal of Advanced Geosciences, 2017)
The Depth-dependent compaction theory that variations in certain geophysical properties with depth; bulk density, formation resistivity together with sonic velocity being a reflection of the pressure regime is the basis for pore pressure prognosis study. Pore pressure prediction (PPP), when done accurately can be used to avert disaster and helps in safe drilling. A porosity-based model has been applied to predict overpressured zones in an onshore environment of the Niger delta basin. Zones with hard overpressures greater than a magnitude of 0.7 psi/ft are generally within 10000ft and below. Top of overpressures for studied wells ranges between 7000ft and 10000ft. Porosities in shale are of typical values ranging between 0.05 to 0.46. A robust concordance between PPP and MPP profiles for each of the wells validates the results here and confirms suitability of model to the studied area.